Assessment of the potential for modal shift to non-motorised transport in a developing context: Case of Lima, Peru. (December 2016) - Ortegon-Sanchez, Adriana; Oviedo Hernandez, Daniel
Abstract: Under the logic of Avoid, Shift, Improve, fostered by donors and NGOs worldwide, cities in the global south are investing emphatically in non-motorised facilities and policies for low-carbon mobility aiming to reduce the adverse environmental impacts of urban mobility. Such is the case of Lima, Peru, our case study. Through the analysis of the potential for integration of non-motorised facilities with current and planned public transport networks, we seek to provide evidence on the planning considerations of non-motorised facilities in Lima with an emphasis on multi-modal travel and integration of non-motorised infrastructure. We develop spatial coverage, capacity and accessibility assessment of the 'supply side' of the transport network. In addition, the research studies the local transport system and travel patterns to identify trips with the potential to shift to non-motorised alternatives. Based on these analyses we estimate indicators of potential coverage, changes in mobility patterns and distributional effects of current investments. Our analysis suggests that coverage of high-capacity public transport can potentially increase by up to six times if integrated adequately with cycling facilities. The research provides methodological and empirical contributions to debates related to the capacity of cities in the global south to adopt low-carbon mobility in the foreseeable future.